Comparison of radiographic outcomes between beta-tricalcium phosphate bone graft and autogenous bone graft in corrective osteotomy of malunited distal radius - Darapongsataporn, MD, Nuttorn; Uerpairojkit, MD, Chairoj (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To compare radiographic outcomes after placement of beta-tricalcium phosphate bone grafts (BPBG) and autogenous iliac bone grafts (IBG) in corrective osteotomy of malunited distal radius fractures with volar locking plates. Materials & Methods: Twenty-seven patients with malunited distal radius fractures were operated on in Lerdsin General Hospital, Bangkok. The inclusion criteria were symptomatic malunited distal radius and unacceptable radiographic parameters. We divided patients into IBG and BPBG groups. We collected radiologic parameters at preoperative, postoperative (4th week), and the last visit. We compared radiographic parameters from both groups by unpaired t-test and calculated radiographic parameters by time sequence in each group by paired t-test. The reoperation rate in both groups was also compared by chi-squared (Fisher exact test). Results: The study did not show a statistical difference in any of the radiographic parameters between the two groups. The union rate was 91.67%, 11 in 12 cases, in the IBG group while the union rate was 80%, 12 in 15 cases, in the BPBG group (p>0.05). The failure correction rate was 8.33%, 1 in 12 cases, in the IBG group while the failure correction rate was 26.67%, 4 in 15 cases, in the BPBG group (p>0.05). Six patients, 1 in the IBG and 5 in the BPBG groups, needed re-operation due to pain or failure to improve functional outcomes. The re-operation rate was 8.33% and 33% in the IBG and BPBG groups, respectively (p>0.05). Conclusion: Radiographic parameters in the BPBG group were not significantly different from the IBG group. Regarding the union and re-operation rate, even though there was no statistically significant difference, there was a tendency of a lower union rate and higher re-operation rate in the BPBG group.